The Role of Teachers’ Professional Competence in Implementing School Based Management: Study Analisys at Secondary School in Parepare City of South Sulawesi ProvinceIndonesia - Lasadike, Syahruddin; Ernawati, Andi; Abdul Rahman, Mohd. Anuar B.; B. Sihes, Ahmad Johari (Institute of Advanced Engineering and Science, 2013)
The relationship between the role of professional competence of teachers and the implementation of School-based Management (SBM) is investigated in this study. Survey and interviews had been done to 325 respondents consisted of 13 principals, 226 teachers, and 86 school committee members of public secondary schools (SMPN) in Parepare, South Celebes, Indonesia in this mixed-method study. The results showed that the there is a significant relationship between the teachers’ professional competence and the implementation of SBM. In other words, the increase of the teachers’ professional competence is significantly related to the increase of the implementation of SBM. Furthermore, the results also indicated that teachers’ professional competence significantly affect the implementation of SBM. Additionally, the qualitative results from the interviews indicated that teachers’ professional development in the form of performance, commitment, and motivation improvement can be considered as an important strategy to improve the quality of SBM.DOI : http://dx.doi.org/10.11591/ijere.v2i3.2577